Development of Shirt Pattern Automation System Using Solid Geometry Approach - Takbir, Muh. Nashir; Jamila, Nur; Justan; Hijriah, Nurul (Cattleya Darmaya Fortuna, 2023)
This study analyzes the partial and simultaneous effects of leadership and compensation on employee performance at the Sitinjak POS office. Utilizing a quantitative approach, data were collected from 21 employees through questionnaires distributed via Google Forms. This research applies hypothesis testing using linear regression analysis with SPSS 25 and Microsoft Excel. The findings indicate that both leadership (X1) and compensation (X2) have a positive and significant impact on employee performance. Furthermore, the simultaneous analysis confirms that leadership and compensation collectively influence employee performance, contributing 63.7% to the overall variance. These results emphasize the importance of effective leadership and fair compensation in enhancing employee productivity and organizational performance.